No Way Out: Severely Abused Latina Women, Patriarchal Terrorism, and Self-Help Homicide. (July 2017) - Harper, Shannon B.
This article explores the diminished occurrence of intimate partner homicide (IPH)—referred to as self-help homicide—perpetrated by Latinas when compared with Black and White women. Self-help homicide is a consequence of patriarchal terrorism . I endeavor to answer the following research question: What explains lower rates of self-help homicide perpetrated by Latinas relative to White and Black women? This question is addressed through a self-help/intersectional theoretical analysis of structural, institutional, and cultural barriers to criminal justice resource access. This diminished access increases the likelihood of IPH victimization.